Synthesis and characterization of inorganic colour pigment from spent acid - Woon H.S.; Nicklaane K.; Ewe L.S.; Lim K.P.; Ismail I.; Tan C.Y. (American Institute of Physics Inc., 2023)
This paper proposes a new method of recycling spent acid from local cold rolling industry into iron oxide pigment that to be applied to the roof tiles. Pickling is a process in which a hot-rolled steel that has rusty scale is dipped into hydrochloric acid prior to further processing. The waste acid contains valuable elements that can be synthesized into iron oxide pigment materials. Through neutralization between a waste acid and three different alkalis namely sodium hydroxide, potassium hydroxide and calcium hydroxide, sludge is formed and further calcined into iron oxide pigment. Colour values include L?ab? were measured using chromameter. X-ray diffraction (XRD) and scanning electron microscopy (SEM) revealed that sodium hydroxide and potassium hydroxide are the suitable alkalis in this study. Calcination at 600C produced red iron oxide pigment materials with good colour properties. 2018 Author(s).